The influence of abusive supervision on employee engagement, stress and turnover intention (REGE Revista de Gestão, 2023)
Purpose – The purpose of this research was to investigate the influence of abusive supervision on work engagement, stress, and turnover intention of subordinates. It was also proposed that work engagement and stress mediate the relationship between abusive supervision and turnover intention. Self-determination theory and the job demands-resources (JD-R) model provide the theoretical framework for our hypotheses.Design/Methodology – The sample of this study consisted of 172 employees from public and private companies operating in different sectors of the economy. The hypotheses were tested through multiple regression analysis.Findings – The results show that abusive supervision negatively influences engagement and contributes to increasing subordinates’ stress and turnover intention. We also found that the relationship between abusive supervision and turnover intention is mediated by engagement, but not by stress.Limitations – Data was obtained from a convenience sample and cannot, therefore, be generalized.Practical implications – The study results suggest that employees are prone to leave an organization when they are subordinated to abusive leaders, corroborating the idea that workers choose organizations but leave their leaders. This, in turn, reinforces the importance of adopting proper leadership selection and training processes.Originality/value – This research addresses the dark side of the relationship between superiors and subordinates, which has been scarcely examined in the Brazilian literature. It also draws attention to different harmful consequences associated with dysfunctional behaviors of professionals that hold leadership positions in organizations.